A Hot Spot for the Interaction of Gating Modifier Toxins with Voltage-Dependent Ion Channels - Winterfield, Jeffrey R. (The Rockefeller University Press, 2000)
The gating modifier toxins are a large family of protein toxins that modify either activation or inactivation of voltage-gated ion channels. ω-Aga-IVA is a gating modifier toxin from spider venom that inhibits voltage-gated Ca(2+) channels by shifting activation to more depolarized voltages. We identified two Glu residues near the COOH-terminal edge of S3 in the α(1A) Ca(2+) channel (one in repeat I and the other in repeat IV) that align with Glu residues previously implicated in forming the binding sites for gating modifier toxins on K(+) and Na(+) channels. We found that mutation of the Glu residue in repeat I of the Ca(2+) channel had no significant effect on inhibition by ω-Aga-IVA, whereas the equivalent mutation of the Glu in repeat IV disrupted inhibition by the toxin. These results suggest that the COOH-terminal end of S3 within repeat IV contributes to forming a receptor for ω-Aga-IVA. The strong predictive value of previous mapping studies for K(+) and Na(+) channel toxins argues for a conserved binding motif for gating modifier toxins within the voltage-sensing domains of voltage-gated ion channels.